2017
DOI: 10.1111/acel.12586
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Cx43/miR21 pathway leads to osteocyte apoptosis and increased osteoclastogenesis with aging

Abstract: SummarySkeletal aging results in apoptosis of osteocytes, cells embedded in bone that control the generation/function of bone forming and resorbing cells. Aging also decreases connexin43 (Cx43) expression in bone; and osteocytic Cx43 deletion partially mimics the skeletal phenotype of old mice. Particularly, aging and Cx43 deletion increase osteocyte apoptosis, and osteoclast number and bone resorption on endocortical bone surfaces. We examined herein the molecular signaling events responsible for osteocyte ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 58 publications
7
123
1
1
Order By: Relevance
“…They can induce changes in multiple cellular processes, including cell proliferation, cell differentiation, and cell senescence (Davis et al., 2017; Jing et al., 2015). However, their instability in the extracellular environment limits their application.…”
Section: Discussionmentioning
confidence: 99%
“…They can induce changes in multiple cellular processes, including cell proliferation, cell differentiation, and cell senescence (Davis et al., 2017; Jing et al., 2015). However, their instability in the extracellular environment limits their application.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, Cx43 deletion from osteocytes renders a phenotype that resembles that of old animals [40] with increased osteocyte apoptosis and enhanced endocortical resorption and periosteal apposition [19,21]. Furthermore, deletion of Cx43 from osteocytic MLO-Y4, but not from osteoblastic Ob-6, cells leads to spontaneous cell death in culture [38]. The later study showed that Cx43 restrains osteocyte death by maintaining the levels of the microRNA miR21, with the consequent reduction of the expression of the phosphatase and tensin homolog PTEN, resulting in the preservation of the Akt-survival pathway.…”
Section: Connexins and Pannexins In Bonementioning
confidence: 91%
“…This study did not find changes in Cx43 mRNA or protein in these osteoblastic cells or in basal gap junction communication, suggesting an intrinsic defect on the function of Cx43 gap junctions in response to parathyroid hormone. However, Cx43 expression in osteocyte-enriched whole bone measured by qPCR and by western blotting [38] and in osteocytes assessed by immunohistochemistry [39] is decreased in old mice. The discrepancy among these studies suggests that the reduction in Cx43 expression with aging likely occurs in osteocytes, and not in osteoblasts.…”
Section: Connexins and Pannexins In Bonementioning
confidence: 99%
“…Interestingly, the ex vivo organ culture model allows the study of the effects of genetic deletions without the need of crossing mice floxed for a particular gene with mice expressing the Cre recombinase, thus reducing costs and time. For instance, in a recent study, calvarial bones from miR21 fl/fl mice were treated with adenovirus‐Cre to delete the miR21 gene . Addition of adenovirus‐Cre decreased miR21 mRNA levels, an effect that, as seen in vivo, was accompanied by decreases in osteocyte viability .…”
Section: Use Of Ex Vivo Bone Organ Cultures For the Study Of Bone Biomentioning
confidence: 99%